Literatur review : protozoa parasit di air sungai - Dhany, Dhany Setya Handary; Tening, Vincentya Aurell Septria Agsant; Mardiono; Khairunnisa; Fitri, Alfiana Aulia Fitri; Gracia, Dora; Silitonga, Jessica Christin; Valentina, Wulan; Putri, Eleventi Oktarina (Program Studi Teknologi Laboratorium Medis, 2024)
River water is potentially unsafe and polluted, which can cause serious infections. Waterborne infections are a major cause of global mortality and morbidity. In cases of diarrhea, this research aims to identify the types of parasitic protozoa and their distribution in waterways in Japan and Indonesia. This research reviews literature by collecting data from various sources, such as books, national and international scientific journals. The articles analyzed are original articles relating to protozoa in river water from both countries. In Japan, protozoa such as Henneguya were found in the Omoi River and Cryptosporidium parvum in several rivers in Hokkaido. In Indonesia, species such as Codonellopsis sp., Favella sp., Tintinnopsis sp., and Codonella sp. are found. in Sorong Regency, as well as various other types in West Bandung, Central Sulawesi and South Kalimantan. The diversity and distribution of protozoa is influenced by water quality, physical conditions, water chemistry, and human activities. This research can provide information regarding protozoa which can act as bioindicators of water quality. The presence and diversity of protozoa can provide an indication of the health condition of aquatic ecosystems. As a result, conservation efforts and management of aquatic ecosystems can be improved.